Assessing Papua New Guinea’s Bid for ASEAN Membership: A Constructivist View - Metherall, Nicholas; Paramma, Paulus; Farneubun, Petrus K.; Renyoet, Claudia C. (Universitas Cenderawasih, 2025)
Papua New Guinea (PNG) has undertaken several steps in order to become a member within ASEAN. However, its bid for membership remains highly contested. This article looks at the reasons why PNG’s admission to ASEAN is unlikely to be approved. Using a qualitative approach with secondary sources and constructivism as a theoretical framework, this article makes the case that, although institutionally and procedurally possible, ASEAN membership is influenced not only by geopolitical and economic (realist and materialist) factors but also by (constructivist) social and normative constructions of belonging. As a result, constructivism becomes the main lens for this article. PNG’s application for membership is therefore unlikely to be accepted in the foreseeable future. An outcome of exclusion may have broader implications. This article will demonstrate that 1) PNG is not located inside the socially constructed regional geographic limits of “Southeast Asia” as defined by ASEAN. 2) PNG’s racialised and culturally unique nature—as a primarily Melanesian culture; and 3) PNG’s foreign policy orientation, which prioritizes their interests over ASEAN’s, is still ingrained in Melanesian and Pacific regional institutions. KEYWORDS ASEAN; Constructivist; Membership; Pacific; Papua New Guinea